2020
DOI: 10.1039/c9tb02932j
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage polarization plays roles in bone formation instructed by calcium phosphate ceramics

Abstract: TCPs recruited more macrophages which polarized towards tissue repair macrophages to create a favourable osteo-immune environment for material-instructed bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 85 publications
0
37
0
Order By: Relevance
“…The different groups of mammary gland tissues were collected and homogenized with PBS on ice, and then the supernatants were collected by centrifugation. The levels of the five inflammatory cytokines were determined by ELISA kits (Multisciences, Hangzhou, China) according to the manufacturer's instructions [53,55].…”
Section: Elisa Assay Of Cytokine Expression Levelsmentioning
confidence: 99%
“…The different groups of mammary gland tissues were collected and homogenized with PBS on ice, and then the supernatants were collected by centrifugation. The levels of the five inflammatory cytokines were determined by ELISA kits (Multisciences, Hangzhou, China) according to the manufacturer's instructions [53,55].…”
Section: Elisa Assay Of Cytokine Expression Levelsmentioning
confidence: 99%
“…Similarly, Zn 2+ deficiency aggravated inflammation, reduced the numbers of M2-polarized M s and increased the numbers of M1-polarized M s [ 31 , 32 ]. In addition, β-TCP was also reported to possess the ability to shift M polarization toward the M2 subtype [ 33 35 ]. M2-polarized M s guide MSC differentiation along the osteogenic pathway and subsequently increase bone mineralization [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, among the different phases of wound healing, several studies have shown that the correct development and understanding of the inflammatory phase, and more precisely of macrophage response, is crucial to achieve a successful tissue regeneration 2 , 3 . Interestingly, different biomaterial properties such as chemical signals, topography or stiffness have shown to modify the macrophage response in cartilage 4 , bone 5 and hernia 6 . Depending on the environmental cues, recruited macrophages can differentiate in different phenotypes, which have been classified in several subsets.…”
Section: Introductionmentioning
confidence: 99%